MEASURING THE OPTIMAL GOVERNMENT SIZE THAT CONTRIBUTE TO ECONOMIC GROWTH OF THE MUSLIM COUNTRIES - Jarita Duasa (Share: Jurnal Ekonomi dan Keuangan Islam, 2018)
The issue of a correct ‘government size’ for economic prosperity of a nation, particularly Muslim nation, is highly linked with the issue of optimal ‘role of state’. The present study attempts to utilise more efficient econometric methods on a sample of Muslim countries over a specific period of time in order to investigate the relationship between government size and economic growth. It also attempts to identify optimal size of government (role of state) that maximise the economic growth of the countries by applying static and dynamic panel estimations on a widely used ‘growth model’ for assessing the impact of government size on economic growth. The findings indicate that a small size of government contributes more to the economic growth of the countries. The results seem to be more robust by using the fixed-effects model as compared to other static or even dynamic models===============================================Pengukuran Ukuran Pemerintah Optimal yang Berkontribusi terhadap Pertumbuhan Ekonomi di Negara-negara Muslim. Persoalan tentang ‘ukuran pemerintah’ yang tepat untuk kemakmuran ekonomi suatu negara, khususnya negara Muslim, berkaitan erat dengan persoalan optimalisasi 'peran negara'. Artikel ini bertujuan mengkaji hubungan antara ukuran pemerintah dengan pertumbuhan ekonomi dengan menggunakan metode ekonometrik yang lebih efisien dengan sampel negara-negara Muslim selama kurun waktu tertentu. Artikel ini juga bertujuan untuk mengidentifikasi ukuran optimal pemerintah (peran negara) yang dapat memaksimalkan pertumbuhan ekonomi negara-negara dengan menerapkan estimasi panel statis dan dinamis dengan menggunakan 'growth model' yang telah banyak digunakan dalam pengukuran dampak ukuran pemerintah terhadap pertumbuhan ekonomi. Hasil kajian menunjukkan bahwa ukuran pemerintah yang kecil dapat memberikan kontribusi lebih besar pada pertumbuhan ekonomi. Hasil kajian lebih meyakinkan dengan menggunakan fixed-effect model dibandingkan dengan model statis atau dinamis.